Aspectos tecnológicos e atividades biológicas do extrato concentrado das fibras do pedúnculo de caju (Anacardium occidentale L.) - Sousa, Jessica Maria Silva (2018)
The concentrated cashew extract (CCE) is obtained from the residual fibers of the peduncle processing through a process that encompasses several technological stages. It has intense yellow coloration, due to the presence of carotenoids, with potential of use as food coloring. In addition, it contains anacardic acids (AA), which although associated with positive biological effects, such as antitumor and antioxidant activity, have also been reported as toxic. Thus, studies on its process of obtaining, stability and toxicity are required. For this, residual fibers were processed to obtain the CCE and samples after the following steps were collected: pressing, centrifugation, microfiltration and pasteurization, being analyzed with respect to the color parameters (L *, a *, b * and ΔE) and content of total carotenoids (TC), total extractable polyphenols (TEP) and AA. Next, the Plackett-Burman (PB) design was used to evaluate the effect of processing and storage variables on the CCE stability. The influence of 8 variables was evaluated: process time; storage temperature; pH; kind of packing; color of the package, in addition to the presence or absence of carboxymethylcellulose, cashew gum or lecithin. A rotational central composite design (RCCD) design was then carried out, in which the process temperature and pH were studied. The process temperature varied from 60 to 90 oC and the pH from 2.5 to 7.0 and the response variables were the color parameters. In parallel, the CCE was atomized and two DCCRs were used, in which cashew gum (CG) or maltodextrin (M) was used as the encapsulating material. The independent variables were: concentration of encapsulant (2-5%) and entry temperature in the atomizer (130-170 oC) and response variables were: hygroscopicity, moisture, solubility (S), color reconstitution (CR), fluidity and retention of total carotenoids (RTC). Concomitantly with the atomization, a lyophilization was carried out, which gave rise to a powdered extract without addition of encapsulants (CCE-L). Thus, CCE-L and CCE-L and CCE-M were evaluated in vivo for their zebrafish toxicity and in vitro for their antiproliferative activity [(glioma (U251), breast (MCF7), multidrug resistant ovary carcinoma (NCI/ADR-RES), lung (NCI-H460), prostate (PC-3), ovary (OVCAR-3), colon (HT-29)], and antimicrobial [Escherichia coli (ATCC 25922), Salmonella Typhimurium (ATCC 51812), Listeria monocytogenes (ATCC 19115) and Staphylococcus aureus (ATCC 25923)]. The results showed that the steps of obtaining the CCE did not cause changes relevant to the final color of the CCE. Initial filtration, centrifugation and pasteurization caused a decrease in TC and TEP, however, did not cause any alteration in AA levels. Microfiltration concentrated TC and AA on CCE. The statistical design of PB showed that the use of less time for the heat treatment and the absence of stabilizers carboximeticelulose, cashew and lecithin are better for CCE stability. In addition, it has been observed that the CCE can be stored out of refrigeration, preferably in glass containers, its color being indifferent, and more compatible with acid matrices. On the other hand, RCCD showed that CCE stability was negatively affected by higher pH and more drastic temperature conditions. The RCCD points for 150 oC and 5% GC and 150 oC and 3.5% M were considered optimal for S and RCA responses, respectively. Scanning electron microscopy (SEM) showed that the microcapsules obtained showed rounded shapes and walls without cracking. However, CG microcapsules presented larger diameters and higher amounts of surface retraction points. In the in vivo toxicity test against zebrafish, CCE did not prove to be toxic for 96 hours of analysis. In the in vitro assays, none of the samples showed antiproliferative activity (IC50 > 250 μg.mL-1); and CCE-L (100 mg.mL-1 and 50 mg.mL-1) was shown to have inhibition halos of 13 and 11 mm, respectively, against L. monocytogenes. The damage caused to this bacterium was confirmed by transmission electron microscopy (TEM). Therefore, the CCE represents a potential and safe source of bioactive compounds for use as an additive in the food industry and can be used in a wide range of products, especially those of high acidity and subjected to mild heat treatment.